“We don’t know Romani, we speak Hungarian”: Language use among Hungarian Roma - Zuzana Bodnárová; Márton A. Baló (Ampersand)
This paper is the first attempt to describe the particular way members of the so-called Romungro group in Hungary may speak Hungarian, which we call the ethnolinguistic repertoire of the Romungros (ERR). We have relied on primary and secondary sources, both published and unpublished, and unstructured sociolinguistic interviews in particular, when looking at the speakers, lexicon, use and function of this speech form. ERR is a form of colloquial Hungarian enriched by some Romani vocabulary and various other ethnolectal features. While it may have come about as a result or side effect of the language shift from Romani to Hungarian, its speakers may also speak inflected Romani. Despite what has frequently been repeated, it is not limited to Romani people whose family have worked as musicians and live in the capital, Budapest. The size of its lexicon varies between speakers and ranges from about 15 to 100 items according to the consultants. While the use of ERR may not necessarily be a conscious choice of its speakers, it can and certainly does, on many occasions, serve to flag identity and express belonging to a specific group and alignment with its values and attitudes.